Fixed drug eruption due to co-trimoxazole: a case report - Dwari, BC; Bajracharya, S; Gupta, S; Mishra, P; Palaian, S; Alam, K; Prabhu, S; Prabhu, M (Journal of Institute of Medicine Nepal, 2007)
Background: Cotrimoxazole is a synergistic fixed dose combination of sulfamethoxazole and trimethoprim used in treatment of several infections including urinary, respiratory, gastrointestinal tract infections. Because of itswide spectrum and low cost it is one of the most preferred antimicrobial in Nepal. Fixed drug eruptions (FDEs) are drug rashes which tend to occur at the same site in the particular patient each time when an offending drug is administered. Co-trimoxazole is a drug commonly implicated for causing FDEs. Case report: We report a case of FDE due to co-trimoxazole occurred in a patient for whom it was prescribed by a local practitioner without taking adequate medication history. We also carried out the causality, severity, preventability and predictability as well as the economic impact of the associated adverse drug reaction (ADR). The report suggests that before prescribing any drug, clinicians should take appropriate medication history and upon occurrence of any ADR the patient should be counseled and instructed to communicate with the clinicians wherever they attend for the next time. Keywords: Causality assessment, Co-trimoxazole, Fixed drug eruption, Naranjo algorithm. The full text of this paper is available at Journal of Institute of Medicine website